Development of Employability Skill Modules to Improve the Employability Readiness of Final-Year Students - Ratna Widiastuti; Citra Abriani Maharani; Eka Kurniawati; Yohana Oktariana (PT Publikasiku Academic Solution, 2023)
The purpose of this research is to reveal whether the employability skills module fulfills the requirements both in material and appearance, and to describe the level of use of the employability skills module to improve the work readiness of final-year students. This research is a Research and Development (R&D) study. Using the ADDIE development model which consists of five stages which include analysis, design, development, implementation, and evaluation. The research was carried out on the Unila FKIP students class of 2019, by conducting research product testing and FGDs. Data were analyzed by descriptive and inferential analysis. The results of the study show that the employability skill module can be used as a medium in increasing the work readiness of final-year students.